MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL DISCOVERY LEARNING PADA MATA PELAJARAN IPAS DI KELAS 4.2 DI MADRASAH IBTIDAIYAH MUHAMMADIYAH UNGGULAN KOTA GORONTALO - Reski Zunaid Sawali; Abd. Hamid Isa; Yulanti Mooduto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
The purpose of this study was to improve students’ learning outcomes through the implementation of the Discovery Learning model in the IPAS subject. This study employed Classroom Action Research (CAR) involving 28 students of class 4.2 at MI Muhammadiyah Unggulan Kota Gorontalo as the research subjects. Data were collected through interviews, observations, tests, and documentation, while data analysis focused on teacher activities, student activities, and students’ learning outcomes. The research was conducted in two cycles, where Cycle I consisted of three meetings and Cycle II consisted of one meeting, and each cycle included four stages: planning, implementation of action, monitoring and evaluation, and analysis and reflection. The results of the initial observation showed that 16 students (57%) achieved mastery; in Cycle I, the number increased to 21 students (75%) who met the minimum mastery criterion (MMC) of 86, and in Cycle II, mastery further increased to 26 students (93%). Therefore, it can be concluded that the implementation of the Discovery Learning model significantly improved students’ learning outcomes in the IPAS subject for class 4.2 at MI Muhammadiyah Unggulan Kota Gorontalo.